146k views
5 votes
PLEASE HELP!!
Let g(x) = -5x + 2 I’m confused

PLEASE HELP!! Let g(x) = -5x + 2 I’m confused-example-1

2 Answers

4 votes

Answer:

g(-1) = 7

Explanation:

this is a function, when it says f(x) or g(x), whatever, and then gives, in this case g(-1), it wants you to substitute -1 into all the x values.

Therefore, our equation is g(-1)= -5 (-1) +2

this simplifies to g(-1)= 7

User Ashish Kumar Verma
by
4.9k points
2 votes

Answer:

7

Explanation:

We need to plug in -1 for x. Here's what we get:


-5(-1)+2 multiplying two negative numbers gives us a positive number


5+2

= 7

User Yinka
by
4.5k points